2002
DOI: 10.1029/2001jd000916
|View full text |Cite
|
Sign up to set email alerts
|

NOy partitioning and budget and its correlation with N2O in the Arctic vortex and in summer midlatitudes in 1997

Abstract: Vertical profiles of the most important species of nocturnal total reactive nitrogen (NOy = NO2 + HNO3 + ClONO2 + 2 N2O5 + HO2NO2) together with its source gas N2O were retrieved from infrared limb emission spectra measured by the Michelson Interferometer for Passive Atmospheric Sounding, Balloon‐borne version (MIPAS‐B) instrument inside the late winter arctic vortex from Kiruna (Sweden, 68°N) on 24 March 1997 and in summer midlatitudes from Gap (France, 44°N) on 2 July 1997. The measured data were compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 53 publications
0
71
0
Order By: Relevance
“…Fahey et al, 1990). Kondo et al (1999) and Wetzel et al (2002) were able to show that their observed anomalous correlation between N 2 O and NO y inside the polar vortex in February and March 1997 was indeed mainly caused by dynamical effects.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Fahey et al, 1990). Kondo et al (1999) and Wetzel et al (2002) were able to show that their observed anomalous correlation between N 2 O and NO y inside the polar vortex in February and March 1997 was indeed mainly caused by dynamical effects.…”
Section: Introductionmentioning
confidence: 79%
“…The precision of retrieved profiles is typically 3-7% and the accuracy reaches 7-15 % (see, e.g. Wetzel et al, 2002).…”
Section: Mipas-bmentioning
confidence: 99%
“…The temperature retrieval 1-σ accuracy is estimated to be within about 1 K. Then, VMR profiles of the target species are individually retrieved in selected spectral regions (see Table 1). A detailed overview on the analysis of nitrogen-and chlorine-containing molecules is given in Wetzel et al (2002Wetzel et al ( , 2010. The error estimation of the target parameter consists of random and systematic errors which were added quadratically to yield the total error which refers to the 1-σ confidence limit.…”
Section: G Wetzel Et Al: Diurnal Variations Of Reactive Chlorine Anmentioning
confidence: 99%
“…Absorption cross-sections of ClONO 2 originate from Wagner and Birk (2003). The microwindows used for the retrieval are basically the ones described by Wetzel et al (2002).…”
Section: Measurement Technique and Data Analysismentioning
confidence: 99%
“…The latter have been mainly based on airborne and spaceborne remote sensing during day-and nighttime in emission or at sunrise and sunset in occultation (e.g. Toon, 1987;Abbas et al, 1991;Sen et al, 1998;Danilin et al, 1999;Osterman et al, 1999;Küll et al, 2002;Stowasser et al, 2002Stowasser et al, , 2003Wetzel et al, 2002;Mengistu Tsidu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%